2019
DOI: 10.3390/nano9111627
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Interface between Hole Transporting Material and Nanocomposite for Highly Efficient Perovskite Solar Cells

Abstract: The performances of organometallic halide perovskite-based solar cells severely depend on the device architecture and the interface between each layer included in the device stack. In particular, the interface between the charge transporting layer and the perovskite film is crucial, since it represents both the substrate where the perovskite polycrystalline film grows, thus directly influencing the active layer morphology, and an important site for electrical charge extraction and/or recombination. Here, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…The observed higher hydrophobicity of the PTAA layer than the SAMs agrees well with a previous report. [39,40] Although it has been well-known that the surface roughness of substrate significantly affected the quality of SAM, [41][42][43] the experimental results from the SEM, EDS, XPS, and contact angle measurements clearly support the formation of a uniform SAM coating on the FTO substrate under the condition used in this study even though the FTO substrate had a higher surface roughness of 43.15 nm compared to 5.64 nm of the ITO substrate as revealed by atomic force microscopy measurements of UV-Ozone treated substrates (see Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The observed higher hydrophobicity of the PTAA layer than the SAMs agrees well with a previous report. [39,40] Although it has been well-known that the surface roughness of substrate significantly affected the quality of SAM, [41][42][43] the experimental results from the SEM, EDS, XPS, and contact angle measurements clearly support the formation of a uniform SAM coating on the FTO substrate under the condition used in this study even though the FTO substrate had a higher surface roughness of 43.15 nm compared to 5.64 nm of the ITO substrate as revealed by atomic force microscopy measurements of UV-Ozone treated substrates (see Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The energy-level alignment of the illustrated structure as a function of each layer is presented in Figure 1b. Depending on provided information, [70,[74][75][76] and data extracted from tauc plots and UV-vis absorption spectra of different types of materials (Figure S1, Supporting Information), P3HT has an unmatched HOMO level (À5.2 eV) with respect to triple cation perovskite (À5.59 eV), which may lead to charge losses at the perovskite/HTL interface. By inserting a PolyTPD layer that has a more promising energylevel alignment (À5.4 eV) as reported in the literature (Figure 1b and S1c,d, Supporting Information), [70,76] the overall cell device performance was improved.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, it was found that the grain sizes of the perovskite crystalline thin films can be increased by decreasing the surface wettability of the substrates [ 140 ]. Therefore, the PTAA and poly[ N , N ′-bis(4-butylphenyl)- N , N ′-bis(phenyl)-benzi (poly-TPD) thin films are widely used as the HTL of the inverted perovskite solar cells [ 141 , 142 , 143 , 144 ]. To completely cover the surface of the roughed ITO thin film, the thickness values of the conjugated polymer thin films are larger than 50 nm.…”
Section: Understanding Of Highly-efficient Inverted Perovskite Solar ...mentioning
confidence: 99%